A New Chinese Economic Order?. (30th July 2020) - Shaffer, Gregory; Gao, Henry
ABSTRACT: China is incrementally developing a new, decentralized model of trade governance through a web of finance, trade, and investment initiatives involving memorandum of understanding, contracts, and trade and investment treaties, supported by an indigenous innovation policy that is transnational in its reach. In this way, China could create a vast, Sino-centric, legal order in which the Chinese state plays the nodal role. It is a hub and spokes model, with China at the hub. In this article, we first examine China's export of an infrastructure-based development model, implemented through Chinese state-owned and private enterprise investments and commercial contracts (Part B), before turning to China's development of a complementary web of free trade and investment agreements (Part C), and an indigenous innovation policy (Part D). The paper theorizes and empirically traces how these Chinese initiatives shape the evolving ecology of the transnational legal order for trade.